Pengaruh Kualitas Sistem Dan Kualitas Informasi AP2T Terhadap Kepuasan Pengguna Di PT. PLN (Persero) Area Kota Bandung Dan Cimahi - Hendrawan, Firman; Sutisna, Ma’mun (Jurnal Riset Bisnis dan Investasi, 2015)
PT. PLN (Persero) Distribusi Jawa Barat dan Banten is one of government company that provides and distribute electricity. System quality and information quality is one important thing that company must see because this will make an impact on user satisfaction of Aplikasi Pelayanan Pelanggan Terpusat (AP2T). the purpose of this research is to know how system quality, information quality and user satisfaction in a company and how much the influence of system quality and information quality toward user satisfaction in PT. PLN (Persero) Bandung and Cimahi Area. The research method which is used is descriptive analysis, classic assumption, multiple correlations, multiple regression and hypothesis testing. The sample in this research as much as 101 respondents. In the data collection is using questionnaire with Likert scale and also interview. Based on the result of data processing, system quality currently in the good category, it can be seen from the ease of use, flexibility, response time, reliability and convenience. Then, information quality also currently on good category, it can be seen from completeness, understandability, accessibility, relevance timeliness and accuracy. The last one is user satisfaction also currently on good category, it can be seen from system satisfaction, information satisfaction, and overall satisfaction. The conclusion of this research is there’s an influence of system quality dan information quality toward user satisfaction amounted 9%.